Design and Development of an Automatic Blower System for Improved Efficiency in Industrial Applications - Shashank Gupta (International Journal of Advanced Robotics and Automation Technology, 2023)
The design and development of an automatic blower system to improve productivity in manufacturing processes are presented in this research article. The suggested system employs advanced control algorithms and sensors to improve the blower's function while minimizing energy usage. The goal of the research is to automate the blower system's operation by incorporating intelligent features, which will decrease the need for human intervention and increase overall efficiency. Experimental results reveal considerable gains in energy efficiency and performance compared to typical manual control approaches. The discoveries of this research contribute to the advancement of automated systems in manufacturing environments, boosting ecologically friendly and advantageous functioning. Scientific advancements have accelerated the technique of machinery advancement to a new level, enabling fully automated manufacturing equipment to enter the market and eventually phase out manual labor. Automation attackers are one of several linked sectors that have grown over the past few years because of the development of industrial automation. The creation of attackers as a new piece of machinery to operate automated production lines can significantly raise the level of automation of manufacturing businesses and increase worker productivity.
Keywords: Automatic blower system; control algorithms; efficiency; energy consumption; industrial applications